The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4315/0362-028x.jfp-16-419
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Escherichia coli on Lettuce under Field Conditions Encountered in the Northeastern United States

Abstract: Although wildlife intrusion and untreated manure have been associated with microbial contamination of produce, relatively few studies have examined the survival of Escherichia coli on produce under field conditions following contamination (e.g., via splash from wildlife feces). This experimental study was performed to estimate the die-off rate of E. coli on preharvest lettuce following contamination with a fecal slurry. During August 2015, field-grown lettuce was inoculated via pipette with a fecal slurry that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
44
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 50 publications
5
44
2
Order By: Relevance
“…In our study, the night time (i.e., between 12 hr (6 p.m.) and 24 hr (6 a.m.) may have allowed adequate time for the bacterial cells to recover from damage and resume their growth. Studies reported that relative humidity and temperature could affect microbial survival or die‐off rate on produce surface (Del Rosario & Beuchat, ; Stine, Song, Choi, & Gerba, ; Weller et al, ). During the current study, the relative humidity ranged from 62% to 74%, and the average temperature ranged from 25 °C to 28.56 °C (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study, the night time (i.e., between 12 hr (6 p.m.) and 24 hr (6 a.m.) may have allowed adequate time for the bacterial cells to recover from damage and resume their growth. Studies reported that relative humidity and temperature could affect microbial survival or die‐off rate on produce surface (Del Rosario & Beuchat, ; Stine, Song, Choi, & Gerba, ; Weller et al, ). During the current study, the relative humidity ranged from 62% to 74%, and the average temperature ranged from 25 °C to 28.56 °C (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…This result was consistent with the results reported by other studies, especially on lettuce surface matrix. In field conditions, Weller et al () observed that the average daily die‐off rate of E. coli on lettuce head was 0.52 log from their 10 days of die‐off study. In a similar study, Bezanson et al () observed an average daily die‐off rate of E. coli O157:H7 on lettuce by 0.56 log.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Produce safety has become the forefront in agricultural issues that address potential public health risks due to an increase in foodborne disease outbreaks (Breitenmoser, Fretz, Schmid, Besl, & Etter, 2011;CDC, 2015;Fan, Annous, Beaulieu, & Sites, 2008;Mazari-Hiriart et al, 2008). Preharvest environment and farm activities are the major sources of microbial contamination in fresh produce (Chhetri, Fontenot, et al, 2019;Weller et al, 2017). Agricultural water is one of the important vehicles for human pathogens (Cooley et al, 2007;Ijabadeniyi, Debusho, Vanderlinde, & Buys, 2011;Park et al, 2012).…”
Section: Introductionmentioning
confidence: 99%